PENGARUH ROLE CONFLICT, ROLE AMBIGUITY DAN ROLE OVERLOAD TERHADAP KINERJA AUDITOR PADA KANTOR AKUNTAN PUBLIK DI KOTA BEKASI - Ayu Fadila; Maidani; Rinjani (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The purpose of this study was to determine the influence of role conflict, role ambiguity and role overload on the performance of auditors at the Public Accounting Firm in Bekasi either partial or simultaneous.. The method used is quantitative. The population in this study are all auditors who worked on Public Accounting Firm in Bekasi with a sample of 55 respondents. Sample selection technique used is purposive sampling method. Source data used are primary data. Methods of data collection using questionnaire survey method and then processed using SPSS version 25. The results of this research show that the variables of role conflict, role ambiguity, and role overload has influence to auditor performance on Public Accounting Firm in Bekasi simultaneously. And the results show that partially, role conflict and role ambiguity have significant influence and negative to auditor performance on Public Accounting Firm in Bekasi, meanwhile role overload have no significant influence to auditor performance on Public Accounting Firm in Bekasi.